Integrated analysis of circRNA-associated ceRNA network in ischemic stroke - Fan, Rongli; Hu, Die; Wang, Maiqiu; Zheng, Huilin; Zhou, Yifeng; Zhang, Lei (Frontiers in Genetics, 2023)
Stroke, of which ischemic stroke (IS) is the major type, is the second leading cause of disability and death worldwide. Non-coding RNAs are involved in the physiology and pathology of IS. The competing endogenous RNA (ceRNA) hypothesis states that circular RNAs (circRNAs) regulate the binding of endogenous microRNAs (miRNAs) to messenger RNAs (mRNAs) by acting as miRNA sponges. However, integrated analyses of circRNAs, miRNAs, and mRNAs in IS are not systemically investigated. In the present study, we constructed a circRNA-miRNA-mRNA ceRNA network aiming to elucidate the pathogenesis of IS. We identified differentially expressed (DE) circRNAs, miRNAs, and mRNAs in IS patients via the Gene Expression Omnibus (GEO) datasets. StarBase and CircBank were used to predict the miRNA targets of DEcircRNAs, and mirDIP, to predict the mRNA targets of DEmiRNAs. We identified hub genes via protein-protein interaction analysis and constructed a core ceRNA sub-network. Finallily, 276 DEcircRNAs, 43 DEmiRNAs, and 1926 DEmRNAs were identified. The ceRNA network included 69 circRNAs, 24 miRNAs, and 92 mRNAs. The core subnetwork included hsa_circ_0011474, hsa_circ_0023110, CDKN1A, FHL2, RPS2, CDK19, KAT6A, CBX1, BRD4, and ZFHX3. In conclusion, we identified hsa_circ_0011474-hsa-miR-20a-5p/hsa-miR-17-5p-CDKN1A as a significant ceRNA axis. Our findings provide new insights into the pathogenesis of IS and offer promising diagnostic and predictive biomarkers.